Manganese availability and transformations in soil profiles under different wheat based cropping systems in north-western India - MITTAL, SHREYANSH; PAL SAINI, SAT; SINGH, PRITPAL (The Indian Journal of Agricultural Sciences, 2022)
Long-term (>10 years) changes in depth-wise distribution of DTPA-Mn and Mn fractions of variable solubility in soils under three different cropping systems, viz. rice-wheat (RWCS), maize-wheat (MWCS) and cotton-wheat (CWCS) in Ludhiana, Ropar and Mansa districts of Punjab, north-western India were studied during 2005–18. The surface (0–15 cm) layer of soils under RWCS had significantly lower (by 31.8%) DTPA-Mn concentration, compared to MWCS. The surface soils under CWCS had 18.4% higher DTPA-Mn than the soils under RWCS. The DTPA-Mn increased significantly with increased depth of soils under RWCS, in contrast to a significant decrease in MWCS and CWCS. A sequential extraction of Mn in different fractions of variable solubility revealed that the surface layer of soils under RWCS had significantly lower concentration, while the lower layers had higher concentration. The Res- Mn fraction comprised the largest proportion (67–70%) of total-Mn in soils under different cropping systems. The (WSEX+SpAD)-Mn fraction was the smallest Mn fraction of high solubility, comprising 2–3% of total-Mn in soils under different cropping systems. The relative distribution of different fractions was OM-Mn≤WSEX-Mn≤SpADMn< AFeOX-Mn<CFeOX -Mn < Ox-Mn< residual-Mn.